Analisis Perbandingan Pencampuran Bijih Nikel High Grade Limonit Dan Low Grade Saprolit Untuk Memenuhi Permintaan Pasar Pada PT Mandiri Mineral Perkasa - Thamsi, Alam Budiman; Yusuf, Firman Nullah; Rahma, Kismu; Hardin Wakila, Muhamad (JNANALOKA, 2023)
PT Mandiri Mineral Perkasa is a contractor company operating in the field of nickel mining and has fulfilled the market/smelter demand requirements for Ni 1.5% - 2.0%, by setting a Cut Of Grade (COG) collection limit of Ni 1.4%. The aim of this research is to determine the Ni content of high grade limonite and low grade saprolite at the research location, and to determine the Ni content of high grade limonite and low grade saprolite, and to determine the additional tonnage and levels to meet market demand. In this study, the blending method was used, a mixing process between different low grade and high grade nickel ores to obtain appropriate mixture results, so that from the results of blending/mixing high grade limonite nickel ore, Ni 1.43 and Fe 26.71% were obtained, and for low grade saprolite you get 1.59% Ni and 26.73% Fe, for the results of blending/mixing high grade limonite and low grade saprolite you get 1.51% Ni and 26.72% Fe, efforts can be made to meet demand Ni 1.8% market with 5,000 tons needs to increase the grade and tonnage, namely, Ni grade 2.32% and 2,111.45 tons.